Next-generation sequencing based detection of BRCA1 and BRCA2 large genomic rearrangements in Chinese cancer patients - Hua, Dingchao; Tian, Qiuhong; Wang, Xue; Bei, Ting; Cui, Lina; Zhang, Bei; Bao, Celimuge; Bai, Yuezong; Zhao, Xiaochen; Yuan, Peng (Frontiers in Oncology, 2022)
BRCA1/2 mutation is a biomarker for guiding multiple solid tumor treatment. However, the prevalence of BRCA1/2 large genomic rearrangements (LGRs) in Chinese cancer patients has not been well revealed partially due to technical difficulties in LGR detection. This study utilized next-generation sequencing (NGS) to analyze the BRCA1/2 mutation profile, including LGR, in 56126 Chinese cancer patients. We also reported that two ovarian and breast cancer patients with NGS-determined BRCA1/2 LGR benefited from PARP inhibitors (PARPi). DNA sequencing identified BRCA1/2 variants (including LGR, pathogenic and likely-pathogenic variants) in 2108 individuals. LGR accounted for 7.8% (70/888) of the total variants in BRCA1 and 1.1% (14/1284) in BRCA2. Among the LGRs detected, exon 1-2 deletion was the predominant LGR (14/70) in BRCA1, and exon 22-24 deletion was the most frequent LGR (3/14) in BRCA2. Notably, the BRCA1 exon 7 deletion was a novel LGR and was identified in six patients, suggesting a specific LGR in Chinese cancer patients. The prevalence analysis of BRCA1 and BRCA2 LGRs across multiple cancers revealed that BRCA1 LGR more frequently occurred in ovarian cancer (1.31%, 33/2526), and BRCA2 LGR was more commonly seen in cholangiocarcinoma (0.47%, 2/425). Two ovarian and breast cancer patients with BRCA1/2 LGR benefited from PARPi therapy. This is the first study to reveal the BRCA1/2 LGR profile of a Chinese pan-cancer cohort by using an NGS-based assay. Two breast and ovarian cancer patients harboring NGS-determined BRCA1/2 LGR benefited from PARPi, indicating that NGS-based detection of BRCA1/2 LGR has the potential to guide PARPi treatment.